101 leadership actions for creating and managing virtual teams - Malone, Ollie (HRD Press, 2004)
These 101 actions will help you manage, lead, or participate in a virtual team; whatever your role you will gain ideas, practices, and suggestions that will enable you to be a more successful team leader. Build your case for virtual teams structure the best possible arrangement for these teams. Manage the people and tools for these teams productively. These 101 actions will help you manage, lead, or participate in a virtual team; whatever your role you will gain ideas, practices, and suggestions that will enable you to be more successful. From strategy and structure to technology and systems,